Pengaruh Work Life Balance Dan Stres Kerja Terhadap Turnover Intention Pada Perawat Di RSI Surabaya - Muhadi Muhadi; Dyan Angesty (Jurnal Keperawatan Muhammadiyah, 2022)
Objective: The purpose of this study is to analyze  The Effect Of Work Stress And Work-Life Balance On Turnover Intention In Nurses at RSI SurabayaMethods: This research method uses descriptive quantitative research methods with a cross sectional approach. Sampling technique using simple random sampling with the number of respondents 128 nurses.  Data collection techniques in this study is to distribute questionnaires to respondents. The analysis technique in this study uses multiple linear regression analysis.Results:  The results of the analysis in this study prove that: work stress and work life balance have a significant effect on turnover intention in nurses at RSI Surabaya.Conclusion:  Work stress and work-life balance have a significant effect on turnover intention. This indicates that the higher the work stress and the low work-life balance of the nurse, the higher the nurse's desire to quit her job (turnover intention)